Analisis Pesan Dakwah dalam Novellet “Ketika Mas Gagah Pergi’ Karya Helvy Tiana Rosa - Diah Hikmah Fitriyah; Zulkifli Lubis; Izzatul Mardhiah (Jurnal Studi Al-Quran, 2016)
The development of the present age experiencing such a big challenge that is crisis morality (moral decadence) as well as social damage. Resulting in a shift in values both religious and social values. This is due to the mass media. Therefore, This research was conducted to examine the contents of messages submitted media to the public, so that people are not trapped by the contents of rhetoric contained in the mass media. This research uses discourse analysis of Teun A. Van Dijk type to know the discourse of moral messages contained in the novel "Ketika Mas Gagah Pergi" and want to know the forms of moral messages contained in the novel.